2015
DOI: 10.1055/s-0035-1568881
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy and Morphology of the Superficial Peroneal Nerve

Abstract: Background Knowledge on the anatomical and morphological characteristics of the superficial peroneal nerve is amenable to further refinement. This cadaveric study aimed to further evaluate anatomical and morphological characteristics of the superficial peroneal nerve. Methods In this study, 10 lower limbs from five fresh cadavers were dissected. The anatomical characteristics of the superficial peroneal nerve were identified. Nerve segments were submitted for histological and morphometric analyses, and nerve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The mean common fibular nerve fascicle number was higher than previously observed 7,11 ; however, these studies used a 12-18 MHZ linear employed UHFUS to assess the superficial fibular nerve in healthy controls, and the mean fascicle count aligned with a prior study using cadaveric inspection. 13 The superficial fibular nerve displayed higher fascicle density compared with common fibular nerve, indicating an increase in fascicular density in the distal segment relative to the proximal segment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The mean common fibular nerve fascicle number was higher than previously observed 7,11 ; however, these studies used a 12-18 MHZ linear employed UHFUS to assess the superficial fibular nerve in healthy controls, and the mean fascicle count aligned with a prior study using cadaveric inspection. 13 The superficial fibular nerve displayed higher fascicle density compared with common fibular nerve, indicating an increase in fascicular density in the distal segment relative to the proximal segment.…”
Section: Discussionmentioning
confidence: 91%
“…9 This enhanced resolution has also been demonstrated in sural nerve studies, aligning with histopathological studies. [8][9][10] However, studies on lower limb nerves have been limited to the use of HFUS transducers, 7,11 performance on cadaveric specimens, [12][13][14] and the absence of healthy controls. 8,10 MRI has not been used to identify individual fascicles of lower limb nerves in healthy individuals.…”
mentioning
confidence: 99%
“…The peroneus brevis branch of the peroneal nerve was only observed in 10% of lower limbs (1/10) in the present study. This might not be due to variation in branching as much as variation in location of nerve bifurcation, which has been reported between 5 and 10 cm distal [6, 32] to the peroneus longus branch. Previous studies have also reported that the distance from the fibular head to the common peroneal nerve was correlated with height [16, 37].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that the most common complication of the arthroscopic Broström procedure is damage to the intermediate superficial peroneal nerve [ 24 ]. Multiple studies have explored the course and distribution of the superficial peroneal nerve [ 25 , 26 ]. However, little is known regarding the location of the intermediate superficial peroneal nerve at the level of the inferior extensor retinaculum, where the intermediate superficial peroneal nerve may be injured during the arthroscopic Broström procedure.…”
Section: Introductionmentioning
confidence: 99%